KOMPETENSI PEDAGOGIK GURU DALAM MENGIMPLEMENTASIKAN MODEL PEMBELAJARAN FIKIH DI MAN II PAMEKASAN - sunu, sunu (Universitas Islam Madura, 2019)
The teacher is one component in the learning process. The teacher has a very important role in determining the quality of learning. Therefore, the teacher must think about and plan for improving the quality of education in every learning activity because the teacher is the key that will determine whether or not educational goals are achieved. For that quality education must be accompanied by qualified teachers so that if we expect quality education, but without improving the quality of teachers it is an illusion. With regard to the context of the above research, the author has conducted research on the pedagogical competence of teachers in fiqh learning in MAN II pamekasan. The research focus was set: (1) What is the teacher's pedagogical competence in understanding educational insights (2) What is the teacher's competence in understanding students (3)What is the pedagogical competence of the teacher in planning fiqh learning (4) What is the pedagogical competence of the teacher in the process of fiqh learning (5) What is the pedagogic competence of the teacher in utilizing fiqh learning technology (6) What is the teacher's pedagogical competence in evaluating results Jurisprudence learning in MAN II Pamekasan.